2011
DOI: 10.4261/1305-3825.dir.4808-11.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of scrotal calculi and its relationship to pain

Abstract: 303T he presence of scrotal calculi is a relatively rare condition that is characterized by the presence of freely mobile calcified bodies between the layers of the tunica vaginalis of the testes, which are often found in patients who have been referred for scrotal ultrasound (1). The etiology of the scrotal calculi is uncertain. However, inflammatory changes within the remnants of the appendix, testis or epididymis may play a role in the development of these types of calculi (1, 2). There are a limited number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 11 publications
(12 reference statements)
1
19
0
1
Order By: Relevance
“…The prevalence of scrotal calculi is thought to be very low in the general asymptomatic population. In a recent study by Tan et al, a scrotal calculus was found in 1.95% of a total of 3,435 patients who were evaluated retrospectively with radiology records. Also, Artaş and Orhan evaluated 868 patients prospectively and found the incidence to be 2.65%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of scrotal calculi is thought to be very low in the general asymptomatic population. In a recent study by Tan et al, a scrotal calculus was found in 1.95% of a total of 3,435 patients who were evaluated retrospectively with radiology records. Also, Artaş and Orhan evaluated 868 patients prospectively and found the incidence to be 2.65%.…”
Section: Discussionmentioning
confidence: 99%
“…On US examination, scrotal calculi are oval or round concretions that can float freely in a hydrocele or appear as a fixed hyperechoic focus with or without acoustic shadowing between the layers of the TVT . Movement of these stones, especially in a hydrocele, helps to differentiate them from other scrotal‐content calcifications, such as in cystoceles and urethroscrotal fistulas .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The term intrascrotal calculi refers to rarely found round or oval loose bodies situated between parietal and visceral lamina of the tunica vaginalis, which are considered benign and without clinical importance 11 , 12 . The reported frequency of these calculi on sonography is approximately 2% 12 , 13 . The frequency is much higher (41%) in patients with coexisting hydrocele 11 .…”
Section: Sonography Of Scrotal Calculi and Pearlsmentioning
confidence: 99%